Analysis of fallacies in Croatian Parliamentary Debate - Kišiček, Gabrijela (Array, 2010)
This research was aimed at analyzing the fallacies in argumentation of Croatian politicians. 20 sessions of Croatian National Parliament (from January 11th 2008 to July 31st 2009) were used as a research material and speeches by Members of Parliament were closely studied in order to find fallacies. The aim of the research was to find out whether there are differences in fallacies between left-wing and right-wing political parties as well as whether there are differences between the party in power and the opposition. There is a clear distinction between left-wing and right-wing parties in Croatia. Taking into consideration that the Left is identified with liberalism and terms such as equality and social justice, while the Right is identified with conservatism and terms such as respect of authority, nationalism, law... the assumption of fallacies characteristic for particular political speeches was made. The hypothesis that left-wing politicians would use argumentum ad misericordiam and the fallacy of neglected alternatives more often than left-wing politicians who would be more likely to use argumentum ad baculum, argumentum ad personam and appeal to authority has been confirmed by the analysis. Furthermore, the politicians in power often use mutatio controversiae or red herring as well as the fallacy of widening the statement. On the other hand, those in opposition tend to use post hoc ergo propter hoc, petitio principii and the fallacy that Weston named false cause. The analysis has shown that some of the fallacies are common to all politicians ; one can say that they are universal in political speaking because they are occasionally being used by the Right and the Left as well as the party in power and the opposition. Such fallacies are argumentum ad populum, argumentum ab utile, exemplum in contrarium, ex concessis, etc.